Static Loading Analysis on Universal Joint Using Solidworks - M Ikhsan; L Edahwati; RD Issafira; W Saputro; AK Faizin; TP Sari; WD Lestari; N Adyono (BIOMEJ, 2022)
This static loading analysis introduction training aims to analyze parts universal joints to the tensile test as an effort to accelerate the improvement of vocational teachers' abilities. In the introduction to analysis training this time using software CAD/CAM ie solidworks which is one software CAD/ CAM which is widely used in the manufacturing industry in terms of designing or analyzing a product design. The training method is carried out by first installing solidworks software to computer equipment, secondly making parts from universal joints, third assembling from parts that have been made, fourth doing drawing 2D from part and assembly that have been made, the five static loading analyzes of universal joint parts with tensile test. Election software this is based on its advantages such as easy to learn, widely used in industry, and can be used as a reference for studying software another. As a result of this training, it is hoped that the teachers of SMK Turen Malang will be able to make part3D models and 2D working drawings.